Implementation of Information Management System on ALS Bus Track Record - Jimmi Akbar; Ihsan Lubis; Fachrul Rozi Lubis; Husni Lubis (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2021)
PT. ALS must pay attention to its operational activities so that operational productivity is able to obtain production results (passengers) in accordance with the company's targets. In this case, factors that need to be considered, such as information management on operational activities that occur on the way from the start to the final destination, so that it can affect the smooth operation. There is a need for management of travel track record information from buses that travel, such as history of machine maintenance, which is a very vital factor in a vehicle, especially buses, and forecasting of spare parts so that the replacement of spare parts can be predicted. The purpose of this study is to convey the track record information of each bus in the Antar Lintas Sumatra company as awhole so that it can be managed effectively which is useful for smooth operations and uses forecasting methods to forecast spare parts using the WMA method